2016
DOI: 10.1186/s12863-016-0452-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure analysis to construct a core collection from a large Capsicum germplasm

Abstract: BackgroundConservation of genetic diversity is an essential prerequisite for developing new cultivars with desirable agronomic traits. Although a large number of germplasm collections have been established worldwide, many of them face major difficulties due to large size and a lack of adequate information about population structure and genetic diversity. Core collection with a minimum number of accessions and maximum genetic diversity of pepper species and its wild relatives will facilitate easy access to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
99
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 40 publications
(61 reference statements)
16
99
6
Order By: Relevance
“…Lee found that C. galapagoense was close to C. annuum (Lee et al, 2016). Our results also support this conclusion, but we also found an interesting conclusion that C. tovarii was also close to C. annuum.…”
Section: Discussionsupporting
confidence: 88%
“…Lee found that C. galapagoense was close to C. annuum (Lee et al, 2016). Our results also support this conclusion, but we also found an interesting conclusion that C. tovarii was also close to C. annuum.…”
Section: Discussionsupporting
confidence: 88%
“…To reduce the effect of the major gene controlling pungency, Pun1 , all accessions were genotyped using the MAP1 marker (Rodríguez‐Maza et al ., ; Stewart et al ., ). A total of 208 accessions were selected, including 140 from the CC240 core collection (Lee et al ., ) and 68 additional accessions (Table S6). Five plants of each accession were grown in plastic greenhouses at the RDA‐GenBank in Jeonju, Republic of Korea.…”
Section: Methodsmentioning
confidence: 99%
“…A subpopulation of Capsicum core collections was used for GWAS (Lee et al, 2016a). To reduce the effect of the major gene controlling pungency, Pun1, all accessions were genotyped using the MAP1 marker (Rodr ıguez-Maza et al, 2012;Stewart et al, 2005).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Phylogenetic reconstruction confirms clustering of accessions in species (Figure 3a), as observed in similar studies based on plant morphological characteristics [27,28] or a smaller number of genetic markers. [3,29,2] Nevertheless, this is to date the largest phylogenetic study in terms of genomic markers analyzed in Capsicum species. We used principal components analysis (PCA) to summarize the observed genetic variation among accessions and species.…”
Section: Resultsmentioning
confidence: 99%
“…inferred from genetic markers mostly reflects the known taxonomic grouping, however it highlights sub-groups within C. annuum and admixture between C. chinense and C. frutescens. [2,3] Even if these studies were carried out on a large number of accessions, both are based on small number of markers (28 simple sequence repeats, SSR, on 1,400 accessions and 48 simple nucleotide polymorphisms, SNP, on 3,800 accessions), therefore the population structure of the different Capsicum species has never been investigated deeply.…”
mentioning
confidence: 99%